Women's experiences of having a Bachelor of Midwifery student provide continuity of care. Issue 3 (June 2016) - Tickle, N.; Sidebotham, M.; Fenwick, J.; Gamble, J.
Abstract: Background: The Australian national midwifery education standards require students to complete a number of continuity of care (COC) experiences. There is increasing evidence outlining the value of this experience to the student, but there is limited research examining women's experiences of having a COC midwifery student. This study aimed to investigates the woman's experiences. Methods: A retrospective descriptive cohort design was used. A paper-based survey was posted to all women cared for by a midwifery student in 2013 ( n = 698). Descriptive statistics were used to explore the proportion, mean score, standard deviation and range of the variables. Construct validity of the Satisfaction and Respect Scales was tested using exploratory factor analysis. Free text responses were analysed using latent content analysis. Result: One-third of women returned a completed survey ( n = 237/698, 34%). There was a significant positive correlation ( p < 0.05) between the number of AN/PN visits a midwifery student attended and women's levels of satisfaction. Women were very satisfied with having a student midwife provide continuity. The qualitative data provided additional insight demonstrating that most women had a positive relationship with the midwifery student that enhanced their childbearing experience. Conclusion: The women in this study valued continuity of midwifery care and were able to form meaningful relationships with their midwifery student. Programs leading to registration as a midwife should privilege continuity of care experiences. Not only does this benefit women but provides the future midwifery workforce with a clear understanding of models that best meet women's individual and the benefits of working in these models.